Therapeutic trough mycophenolic acid levels positively correlate with omega-3 fatty acids in leukocytes of children with idiopathic nephrotic syndrome. a pilot study - Turolo, Stefano; Edefonti, Alberto; Syren, Marie-Louise; Bellotti, Anita S.; Morello, William; Collino, Federica; Agostoni, Carlo; Montini, Giovanni (Frontiers in Pharmacology, 2025)
The pathogenesis of idiopathic nephrotic syndrome (INS) in most pediatric cases involves immune cell dysfunction, mediated, among other factors, by biologically active polyunsaturated fatty acids -dependent compounds in the blood and cell membranes. The immunosuppressive drug mycophenolate mofetil (MMF) is commonly used to maintain remission in patients with steroid-dependent nephrotic syndrome. The aim of this pilot study was to investigate the effect of trough blood mycophenolic acid (MPA) levels on the endoleukocyte fatty acid omega-3 and omega-6 series. Eighteen pediatric subjects with INS were enrolled, including 12 steroid-sensitive and 6 steroid-resistant children. Fatty acid (FA) profile was analyzed by gas-chromatography, and MPA blood level was evaluated by immunometric assay. Among steroid-sensitive patients, a positive correlation was observed between endoleukocyte omega-3 FA (n-3) and trough blood MPA levels, and a negative correlation was found between endoleukocyte omega-6 FA (n-6) and trough blood MPA levels. In addition, a positive correlation was found between endoleukocyte anti-inflammatory DHA and trough blood MPA levels. In contrast, in steroid-resistant subjects no correlation between endoleukocyte n-6/n-3 ratio and trough blood MPA levels was observed. In conclusion, adequate trough MPA drug levels may have contributed to switch the FA pathway to a more favorable endoleukocyte n-6/n-3 ratio and DHA levels, possibly supporting the natural anti-inflammatory activities of n-3 FA. In steroid-resistant NS, despite adequate MPA levels, no promotion of the anti-inflammatory activity of the n-3 series was found.